2022
DOI: 10.5435/jaaosglobal-d-21-00308
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Versus In-person Grand Rounds in Orthopaedics: A Framework for Implementation and Participant-reported Outcomes

Abstract: Introduction: Grand rounds have been weekly gatherings at academic orthopaedic surgery programs across the country for decades. During the 50th year of grand rounds at our institution, the COVID-19 pandemic prompted the transformation of this in-person forum into a virtual setting. The purpose of this study was to detail this initiative and to report survey data providing participant-reported perceptions and satisfaction of virtual versus in-person grand rounds. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This study compares differently delivered but nearly identical programs in equity-centered leadership training for physicians and indicates that the experience can be equally impactful whether the format is virtual or in-person. Our findings were similar to those of Nilaad et al 28 , when studying live virtual vs in-person pharmacy curriculum learning outcomes in medical and pharmacy students or to the team of Reddy et al 29 , when examining the acceptability of virtual vs in-person grand rounds. The data here show that participants responded positively in both situations and reported similarly large learning gains.…”
Section: Discussionsupporting
confidence: 87%
“…This study compares differently delivered but nearly identical programs in equity-centered leadership training for physicians and indicates that the experience can be equally impactful whether the format is virtual or in-person. Our findings were similar to those of Nilaad et al 28 , when studying live virtual vs in-person pharmacy curriculum learning outcomes in medical and pharmacy students or to the team of Reddy et al 29 , when examining the acceptability of virtual vs in-person grand rounds. The data here show that participants responded positively in both situations and reported similarly large learning gains.…”
Section: Discussionsupporting
confidence: 87%
“…Although 51.4% of trainees favored virtual learning, attendings were more disapproving with only 32.2% favoring virtual learning 74 . Virtual grand rounds were more convenient to attend and participants were more satisfied with the virtual format compared with in-person grand rounds 79 . However, in-person grand rounds were perceived as more effective for facilitating collaboration between presenters and participants, promoting networking, and retaining audience attention 79 .…”
Section: Resultsmentioning
confidence: 99%
“…Although some respondents reported that they preferred the convenience of online learning, others expressed dissatisfaction with the quality of virtual education compared with in-person instruction 14,[67][68][69][70][71]74,79,86,89 . One common theme was that residents found it difficult to fully engage with online lectures, with many reporting a lack of interaction and difficulty maintaining attention 14,[67][68][69][70][71][72]74,79,86,89 . Virtual methods of education can be effective, but they may not be a perfect substitute for in-person teaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While MGR attendance patterns for in-person conferences have been reported [ 3 ], the impact of remote conferences on faculty attendance at MGR is unknown. The analysis of remote surgical conferences [ 4 , 5 ] has been limited by sample size and aggregate data.…”
Section: Introductionmentioning
confidence: 99%